Effects of Submarine-Cable Types and Parameters on Performance of a Future-Scheduled Offshore Wind Farm Connected to Taiwan Power System - Wang, Li; Kuan, Bing-Lin; Yu, Chien-Hsiang; Wu, Hong-Yi; Zeng, Shi-Ying; Prokhorov, Anton V.; Mokhlis, Hazlie; Huat, Chua Kein (Institute of Electrical and Electronics Engineers, 2020)
Submarine cables are indispensable for offshore wind farms (OWFs) connected to a power grid. The submarine cable can cause certain degrees of impact on the system performance due to its different lengths, characteristics, electrical parameters, etc. This paper employs the power-system simulation software of Power System Simulator for Engineering (PSS/E) for modeling a future-scheduled OWF, i.e., a large-scale doubly-fed induction generator-based OWF of 200 MW, connected to Jang-Bin distribution substation of Taiwan Power System through five feeders, five circuit breakers, two step-up power transformers, a commercial submarine cable, and an underground cable. This paper simulates and compares the electrical quantities of the studied OWF with different operating capacities under various lengths of three types of commercial submarine cable. The transient surge peak voltages at the common bus of the OWF and the bus of Jang-Bin distribution substation subject to the switching of one of the five circuit breakers of the studied OWF under different lengths of the three types of commercial submarine cable are also compared using the power-system simulation software of ATPDraw in Alternative Transients Program (ATP) version of Electromagnetic Transients Program (EMTP). © 1972-2012 IEEE.